Comparison of Myocardial Protection Effects Between Enriched Crystalloid Cardioplegia Solution and St. Thomas Solution: An Experimental Study on Oryctolagus cuniculus - Rahman, Aditya; Sembiring, Yan Efrata; Suta Winarno, Dhihintia Jiwangga (Journal of Neonatal Surgery, 2025)
Background: Cardioplegic solutions are critical for myocardial protection during cardiac surgery. Enriched Crystalloid Cardioplegia (ECC), modified from the St. Thomas solution with added mannitol, MgSO₄, and lidocaine, may enhance protection. This study conducted to compare the myocardial protection efficacy of ECC and St. Thomas solution in rabbits during ischemia Methods: Eighteen male Oryctolagus cuniculus rabbits were randomized into three groups (n=6 each): ECC, St. Thomas, and control (Ringer Lactate). Cardioplegia was administered via antegrade aortic root infusion (15 mL/kg, 25°C, single dose). After 90 minutes of aortic cross-clamping, myocardial tissues were collected at 30, 60, and 90 minutes for histological evaluation using H&E staining. Outcome measures included myocardial injury score, extent of damage, and neutrophil infiltration. Results: ECC showed significantly lower injury scores at 30 and 60 minutes compared to control (p= 0.027 & p= 0.018). No significant difference was found between ECC and St. Thomas. At 90 minutes, differences were not statistically significant. No significant differences were observed in infarct size or neutrophil infiltration between groups. Conclusion: ECC offers myocardial protection comparable to St. Thomas solution, with a trend toward prolonged efficacy. Its additional agents may enhance protective mechanisms during cardiac arrest